Forecasting the Price of Cayenne Pepper in the Surabaya City - Putra, Joshua Eka; Perwitasari, Hani; Jamhari, Jamhari (Department of Agribusiness Halu Oleo University Kendari Southeast Sulawesi, 2021)
The price fluctuation of cayenne pepper in Indonesia is relatively high. Price fluctuations have an impact on consumers significantly when prices increase. This causes consumers to find it challenging to fulfil their daily needs for chilli. The effects of price fluctuations for farmers, namely: farmers have difficulty making production decisions. This causes the risk of cayenne pepper farming to become high. Predicting the price of cayenne pepper in the future is an effort to minimize the risk of cayenne pepper farming and industries requiring cayenne pepper. This study aims (1) to determine the forecasting model for cayenne pepper prices in Surabaya City (2) to predict the price of cayenne pepper during the period January 2020 - June 2020 in the Surabaya City using the ARIMA method. The analyzed data is cayenne pepper prices from July 2010 to December 2019 sourced from the Badan Pusat Statistik (BPS). The analysis results show that the best ARIMA model in estimating the price of red chilli in Surabaya is ARIMA (1,0,1), with a MAPE of 3.84%. The forecast results for the price of cayenne pepper in Surabaya are proven and have decreased.